Penerapan Penjatuhan Hukuman Kebiri Kimia Serta Tata Cara Eksekusinya pada Pelaku Kejahatan Pelecehan Seksual terhadap Anak - Nashru Nazar Rosyidi; Oci Senjaya (Universitas Batanghari Jambi, 2021)
Nowadays, there are more and more crimes of child sexual abuse in Indonesia. Children should be protected by the government in order to become the nation's next generation. In 2019, the Mojokerto District Court sentenced the defendant Aris (20) who was convicted of a crime of sexual abuse against a child and this verdict was the first verdict in Indonesia to impose chemical castration on perpetrators of crimes of sexual abuse against children. This writing uses the juridical-normative method which looks at empirical data as a reference for writing this journal. For some parties, chemical castration punishment is considered effective in punishing perpetrators of crimes of child sexual abuse so that it becomes a frightening thing for other perpetrators of sexual abuse crimes. This is included in the category of the theory of the purpose of punishment in order to create order and order in society. Perppu Number 1 of 2016 is the legal basis for the application of chemical castration punishment. However, there are many pros and cons to castration. One of the things that has created contra is contrary to the ratification of human rights. Considering that Indonesia is a state based on the rule of law, which is obliged to protect human rights guarantees as stated in Article 28 I of the 1945 Constitution of the Republic of Indonesia.